Agricultural public spending in Africa is low and inefficient - Benin, Samuel (World Bank, 2017)
Analyzes the patterns of agricultural public spending in Africa, in comparison with other forms of public spending, across different developing regions of the world, and provides evidence on the returns to public spending in the agricultural sector in Sub-Saharan Africa. Between 1980 and 2012, total agricultural spending in Africa increased at an average rate of 0.8 percent a year and constituted 4 percent of total spending (far below the 10 percent spending target) and 4.7 percent of agricultural valued added. The returns vary for spending on different agricultural functions, 22–55 percent for research, 8–49 percent for extension, and 11–22 percent for irrigation. The higher returns to agricultural research spending (93 percent) than to total agricultural spending (11 percent) reflect the low and declining research spending intensities in the continent. The return to total agricultural spending increased with the number of years that countries have been participating in Comprehensive Africa Agriculture Development Programme (CAADP).